2003
DOI: 10.1128/aem.69.1.170-176.2003
|View full text |Cite
|
Sign up to set email alerts
|

Coevolution of Bacteriophage PP01 and Escherichia coli O157:H7 in Continuous Culture

Abstract: The interaction between Escherichia coli O157:H7 and its specific bacteriophage PP01 was investigated in chemostat continuous culture. Following the addition of bacteriophage PP01, E. coli O157:H7 cell lysis was observed by over 4 orders of magnitude at a dilution rate of 0.876 h ؊1 and by 3 orders of magnitude at a lower dilution rate (0.327 h ؊1 ). However, the appearance of a series of phage-resistant E. coli isolates, which showed a low efficiency of plating against bacteriophage PP01, led to an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
181
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(188 citation statements)
references
References 26 publications
(44 reference statements)
5
181
1
Order By: Relevance
“…Under the GFG framework, parasites must match or exceed the host's resistance alleles at each locus to have a high probability of causing an infection, which naturally leads to the evolution of generalism in the form of broader resistance and infectivity ranges. These dynamics have been observed in a variety of real host-parasite relationships, including bacterium-phage (Bohannan and Lenski 2000;Buckling and Rainey 2002a;Mizoguchi et al 2003;Brockhurst et al 2006;Forde et al 2008;, plant-pathogen (Flor 1956;Thompson and Burdon 1992;Thrall and Burdon 2003) and nematode-bacterium systems (Schulte et al 2010). Recent studies of bacterium-phage coevolution have found that infectivity range is correlated with the number of amino acid changes in tail fibers relative to the ancestral genotype , providing further support for the GFG framework.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Under the GFG framework, parasites must match or exceed the host's resistance alleles at each locus to have a high probability of causing an infection, which naturally leads to the evolution of generalism in the form of broader resistance and infectivity ranges. These dynamics have been observed in a variety of real host-parasite relationships, including bacterium-phage (Bohannan and Lenski 2000;Buckling and Rainey 2002a;Mizoguchi et al 2003;Brockhurst et al 2006;Forde et al 2008;, plant-pathogen (Flor 1956;Thompson and Burdon 1992;Thrall and Burdon 2003) and nematode-bacterium systems (Schulte et al 2010). Recent studies of bacterium-phage coevolution have found that infectivity range is correlated with the number of amino acid changes in tail fibers relative to the ancestral genotype , providing further support for the GFG framework.…”
Section: Introductionmentioning
confidence: 92%
“…This means that contemporary populations may be well adapted to ancestral lineages but perform poorly against future populations (Buckling and Rainey 2002a;Mizoguchi et al 2003;Scanlan et al 2011). The fundamental principles of these "coevolutionary arms races" are captured by the gene-for-gene (GFG) framework, in which hosts can avoid infection by accumulating resistance alleles at multiple loci but parasites can counter these adaptations by gaining infectivity alleles at matching loci (Flor 1956;Sasaki 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In plant systems, a COR to herbivory often involves increased allocation of nutrients to secondary compounds used to deter grazing pressure (Bergelson and Purrington, 1996;Siemens et al, 2003), suggesting that a COR may be expressed more in nutrient-limited environments. For bacteria, it is assumed that virus resistance often involves the modification of pilus structure or another surface receptor molecule (Lythgoe and Chao, 2003;Mizoguchi et al, 2003). Such mutations may decrease host fitness by reducing nutrient uptake rates, thus influencing competitive interactions.…”
Section: Detecting a Cor In Synechococcusmentioning
confidence: 99%
“…Phage-resistant mucoid mutants have been observed previously in E. coli and other bacteria (Hancock and Reeves, 1975;Mizoguchi et al, 2003;Scanlan and Buckling, 2012). Mucoidy is caused by mutations that increase production of extracellular polysaccharides (Sapelli and Goebel, 1964;Lieberman and Markovitz, 1970).…”
Section: Discussionmentioning
confidence: 93%